Inflation persistence during periods of structural change: an assessment using Greek data - George Hondroyiannis; Sophia Lazaretou (European Central Bank (ECB), 2004)
The paper estimates inflation persistence in Greece from 1975 to 2003, a period of high variation in inflation and changes in policy regimes. Two empirical methodologies, univariate autoregressive (AR) modelling and second-generation random coefficient (RC) modelling, are employed to estimate inflation persistence. The empirical results from all the procedures suggest that inflation persistence was high during the inflationary period and the first six years of the disinflationary period, while it started to decline after 1997, when inflationary expectations seem to have been stabilised, and thus, monetary policy was effective at reducing inflation. Empirical findings also detect a sluggish response of inflation to changes in monetary policy. This observed delay seems to have changed little over time.
Keywords: E31; E37; 330; CPI inflation; Persistence; structural change